Measuring Patient Safety in the Emergency Department. (March 2014) - Pham, Julius Cuong; Alblaihed, Leen; Cheung, Dickson Sui; Levy, Frederick; Hill, Peter Michael; Kelen, Gabor D.; Pronovost, Peter J.; Kirsch, Thomas D.
As a safety net for the health care system, quality and safety performance in emergency medicine (EM) is important for policy makers, insurers, researchers, health care providers, and patients. Developing performance indicators that are relevant, valid, feasible, and easy to measure has proven difficult. To monitor progress, patient safety should be measured objectively. Although conceptual frameworks and error taxonomies have been proposed, a practical scorecard for measuring patient safety over time in EM has been lacking. This article proposes a framework that measures safety through 4 major domains: (1) how often patients are harmed, (2) how often appropriate interventions are delivered, (3) how well errors in the system are identified and corrected, and (4) emergency department (ED) safety culture. Examples of specific measures for each of these domains are provided, but the EM community should reach consensus on what measures are important for the ED environment and patients.